POTENSI SUMBER OPEN KNOWLEDGE MELELUI OPEN GOVERNMENT : STUDI KASUS PADA PERPUSTAKAAN KHUSUS KEMENTERIAN LEMBAGA - Irhamni Irhamni (Perpustakaan Nasional RI, 2019)
The Open Knowledge and Open Government movements have been initiated and have recently caused a lot of data in a government institusion. The government of Indonesia through the Open data Initiative movement has launched a number of roadmaps on the implementation of open data in Indonesia by involving Ministries/Institutions. At present there are only few reserach regarding goverment publications in libraries and their role and function in the implementation of open government. This research was conducted to see the potential of open knowledge resourch throug open government in special ministry/institution libraries by looking at several aspect. The methodology used in this study is descriptive analysis by looking at the distribution of information through proactive information dissemination by promoting information and public involvment, speed of access, decreasing processingdeman costs, and ready acess to government information. The result of the study show that there haven been a lot of diversity in the data publication, as well as in the distribution of information and feedback as well as responses from the Ministry / Institution Library. The potential for implementing open knowledge resulted from the implementation of open government data in Ministries / Institusion in very large needs to be extensively applied to regional work units.